The great mimicker “Burkholderia cepacia”: A case of intra-abdominal abscesses - Divya Prabhu; Guru Prasad Ravikumar; Ashwin Kulkarni; Megha Gopal (Journal of Krishna Institute of Medical Sciences University, 2023)
Burkholderia cepacia infections are underreported and often seen in immunocompromised or cystic fibrosis patients. We describe a case of intra-abdominal abscesses and bacteraemia due to Burkholderia cepacia in a non-cystic fibrosis patient. A middle aged farmer with uncontrolled diabetes presented with 1 month of fever, abdominal pain, anorexia and weight loss. Examination revealed hepatosplenomegaly. Imaging showed multiple abscesses in liver and spleen. Burkholderia cepacia grew in the blood cultures. Patient showed clinical and radiological resolution post treatment with meropenem and subsequently co-trimoxazole. Clinicians' awareness, targeted investigations and early therapeutic intervention are essential for diagnosis and management of Burkholderia cepacia infections.